If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 5x = 9 + 3x Solving 3 + 5x = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 5x + -3x = 9 + 3x + -3x Combine like terms: 5x + -3x = 2x 3 + 2x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + 2x = 9 + 0 3 + 2x = 9 Add '-3' to each side of the equation. 3 + -3 + 2x = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 9 + -3 2x = 9 + -3 Combine like terms: 9 + -3 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 1/2(2x-4)=3x+5/6 | | [3v-2]/5=4 | | 9y-5-6y+1=0 | | 35-7x=9(3x+3) | | (4x^2+3)(x-4)(x+4)=0 | | 8y+13=5y-5 | | (y+.33)(y-.33)= | | [1-6n]+3=46 | | 5x^2-6x+5= | | 0.1(x+250)=5,000 | | 8x^5+26x^3-24x=0 | | x=1056-.1x | | 7(z-5)+1=2-3(2z-1) | | 2x+6x-14=22 | | [4x+4]=28 | | 12+x=-3x(4-x) | | 6(2x-5)=12 | | -118-3x=77+12x | | 12x+x=-3x(4-x) | | [-7x+4]=18 | | 2(6x+2)=-(2x-10) | | C=3ab | | (x+0.2)(x-0.2)= | | -11a-17a+11a+10a+-2a=18 | | 4x-37=x+35 | | 1/2+3/2=3 | | C=3pieab | | 20x-16=4x+ | | -9x+13=5 | | 18t-13t-t-3t=12 | | 3+2z-1=7z+7-42 | | 18-17x=-20.5 |